2018
DOI: 10.3390/molecules23051188
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Hepatoprotective Potential of Quercetin 7-Rhamnoside In Vitro and In Vivo

Abstract: Hypericum japonicum is traditionally used as a folk medicine to treat cholestasis and hepatitis. Quercetin 7-rhamnoside (Q7R) is one of the main flavonoid components of Hypericum japonicum and has been rarely studied. The aim of the present study was to evaluate the antioxidant activity and hepatoprotective potential of Q7R. In the in vitro experiments, DPPH, ABTS and ferric reducing antioxidant power (FRAP) assays were first performed to assess the antioxidant properties of Q7R, and then a H2O2-induced oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…The levels of serum AST, ALT and LDH activities reects damage to hepatocytes and were considered to be highly sensitive and fairly specic preclinical and clinical biomarkers of hepatotoxicity. 46 It is exciting that high dose (200 mg kg À1 ) and medium dose (100 mg kg À1 ) of compound 38c show good protection, which can reverse the increase of AST, ALT, LDH in serum caused by CCl 4 , the current results are also consistent with previous reports. GSH, an important part of the main defense system, can scavenge free radicals in the body.…”
Section: Discussionsupporting
confidence: 91%
“…The levels of serum AST, ALT and LDH activities reects damage to hepatocytes and were considered to be highly sensitive and fairly specic preclinical and clinical biomarkers of hepatotoxicity. 46 It is exciting that high dose (200 mg kg À1 ) and medium dose (100 mg kg À1 ) of compound 38c show good protection, which can reverse the increase of AST, ALT, LDH in serum caused by CCl 4 , the current results are also consistent with previous reports. GSH, an important part of the main defense system, can scavenge free radicals in the body.…”
Section: Discussionsupporting
confidence: 91%
“…In Artemisia annua, hepatoprotective activity is connected to their content of hydroxycinnamoyl quinic acids and flavonoids. 42 An important mechanism of hepatoprotective activity is related to its ability to transfer hydrogen to free radicals, activate antioxidant enzymes, and inhibit oxidases 43 . Methanol is the solvent capable of extracting the greatest amount of phenolic compounds 44 , a type of compound that presents a high antioxidant capacity that is present in A. absinthium 45 , however, bioguided phytochemical prospecting is required to determine the metabolite(s) responsible for this activity and its subsequent determination of its mechanism of action by which it exerts its pharmacological action.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that excess free radicals play a key role in the development and progression of liver injuries [ 17 ]. Thus, natural antioxidants have attracted attention for their safety, by preventing oxidative liver injuries, and the dietary consumption of antioxidants is recommended to prevent liver diseases [ 18 ]. Thus, we investigated the hepatoprotective effect of MES on t -BHP-treated HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%